FRI0132 EFFICACY AND SAFETY OF SWITCHING JAKINIBS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Retuerto-Guerrero, M.; Trujillo, E.; Valero, C.; Fernandez-Espartero, C.; Soleto, C. Y.; García-Valle, A.; Aurrecoechea, E.; Garijo Bufort, M.; López Robles, A.; Loricera, J.; Pablos, J. L.
Abstract : Background: Different Jakinibs (JAKi) have shown efficacy in rheumatoid arthritis (RA) but in an important proportion of patients, insufficient response leads to therapy withdrawal. The different JAKi show variable selectivity for the four Jak isoforms (Jak1, 2, 3 y Tyk2) but there are no clinical trials analyzing the response to a JAKi after the suspension of another JAKi and therefore, observational data may be useful in this regard. Objectives: To describe efficacy and safety of the second JAKi in patients with suspension of the first due to failure or side effects. Methods: Spanish observational multicentric study. Data were retrospectively obtained from medical records of 28 patients with RA sequentially treated with baricitinib o tofacitinib in any order. Results: We identified 28 patients with RA treated with baricitinib and tofacitinib. Patient´s characteristics are summarized in Table 1 . Half of the patients received tofacitinib first, and the other half baricitinib as the first JAKi. Mean survival for the first JAKi was 7, 6 ± 6, 1 months. The reason for withdrawal was inefficacy in 17 cases (61%) and adverse effects in 11 (39%). Mean follow-up after starting on the second JAKi was 9, 6 ± 5, 6 [3-19] months. Disease activity data along follow-up are depicted in Table 2 . Survival on the second JAKi was 82% at 3, 76% at 6, and 62% at 12 months when 13 of the 21 patients maintained the therapy. In all 8 patients who discontinued the second JAKi, the reason was inefficacy. The treatment suspension rate was similar among patients discontinuing the first JAKi for inefficacy (n=5, 29, 4%) or for adverse effects (n=3; 27, 3%). Conclusion: Our data show that therapy with a second JAKi is a safe and efficacious option after discontinuation of the first JAKi due to either inefficacy or side effects. The response rate to the second JAKi is similar in patients with inefficacy or side effects which suggests that failure to the first does not reduce the chance of response to the second. Acknowledgments: M. Retuerto was recipient of a training grant from Sociedad Española de Reumatología (SER). Disclosure of Interests: None declared